Stability differences of quality traits in high-quality hybrid rice - Jiaxin Xie; Zhengwu Xiao; Xing Li; Fangbo Cao; Jiana Chen; Izhar Ali; Anas Iqbal; Abdul Wahab; Min Huang (Journal of Agriculture and Food Research)
Rice breeders have developed numerous hybrid rice varieties with high yield and improved quality over the years. However, limited information is available on the stability of quality traits in high-quality rice. This study determined the stability of quality traits in two high-quality hybrid rice varieties, Zhuliangyou 570 (ZLY570) and Huazheyou 261 (HZY261), across different ecological regions and agronomic practices through on-farm research and field experiments. The on-farm research was conducted across nine provinces in southern China in 2021–2023, and field experiments with two sowing dates and six nitrogen treatments were performed in Hunan Province in 2022 and 2023. Results indicated that in both on-farm research and field experiments, both varieties exhibited a high coefficient of variation (CV) in chalky grain rate and chalkiness degree, followed by head rice rate, amylose and protein contents, traits including brown and milled rice rates, and length-to-width ratio revealed a low CV. The chalky grain rate and chalkiness degree of both varieties displayed poor stability, followed by head rice rate and amylose content. In contrast, brown and milled rice rates, length-to-width ratio, and protein content demonstrated high stability in the genotype plus genotype × environment interaction biplot analysis. However, the maximum value of chalky grain rate and chalkiness degree were only 8.43 % and 1.83 % for ZLY570, and 9.12 % and 2.05 % for HZY261, respectively. Both varieties revealed a high range (R) in head rice rate and amylose content, but a low R in protein content. Furthermore, the head rice rate and amylose content varied widely, while protein content showed narrower variability. These results suggest that high-quality hybrid rice exhibits poor stability in terms of head rice rate and amylose content. In contrast, it demonstrates relatively high stability in brown and milled rice rates, length-to-width ratio, chalky grain rate, chalkiness degree, and protein content.